2017
DOI: 10.1155/2017/5896191
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Usage in the Soil Quality Degradation Potential in Wanasari Subdistrict, Brebes, Indonesia

Abstract: Uncontrolled application of pesticides can contaminate soil and may kill other nontarget organisms. This study aims to determine the usage pattern of pesticides by farmers in Wanasari Subdistrict and study the soil quality degradation potential. This study was a quantitative and qualitative research. Sources of data were collected from observation, questionnaire, and in-depth interview methods. The respondents were shallot farmers who planted shallot during 2013-2016 ( = 60). In-depth interview was done with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 14 publications
0
40
3
3
Order By: Relevance
“…Wanasari District as the region with the highest onion production in Brebes Regency is able to produce 1,025,680 Kw, the average production is 144.97 Kw / ha [1]. According to previous research conducted by Joko T, et al (2017) that onion farmers in Kecamatan Wanasari use large amounts of pesticides, and average to apply pesticides every three or four days. The use of pesticides in large numbers is due to onion plants are very vulnerable to pests, so farmers must apply insecticides to prevent damage to the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wanasari District as the region with the highest onion production in Brebes Regency is able to produce 1,025,680 Kw, the average production is 144.97 Kw / ha [1]. According to previous research conducted by Joko T, et al (2017) that onion farmers in Kecamatan Wanasari use large amounts of pesticides, and average to apply pesticides every three or four days. The use of pesticides in large numbers is due to onion plants are very vulnerable to pests, so farmers must apply insecticides to prevent damage to the plant.…”
Section: Introductionmentioning
confidence: 99%
“…The use of pesticides in large numbers is due to onion plants are very vulnerable to pests, so farmers must apply insecticides to prevent damage to the plant. In his research, Joko T, et al (2017) showed that found farmers who use insecticides class of organophosphates with chlorpyrifos active ingredients [2].…”
Section: Introductionmentioning
confidence: 99%
“…N = population. e = the limit of tolerance (0.05) Therefore, n = 30,229 = 30,229 = 30,229 = 30,229 1 + 30,229(0.05) 2 1 + 30,229(0.0025) 1 + 75.5 76.5 n = 390 respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Sequel to application of these chemical compounds on farm lands to achieve the essential mission to care for crops, they have been reported also to compromise water quality [1]. They move into the surrounding water bodies, therefore having a widespread effect on the physical, chemical and biological processes within aquatic ecosystems [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dampak negatif yang terjadi terhadap manusia dan lingkungan disebabkan oleh perilaku petani yang kurang bijaksana. Petani mengaplikasikan pestisida setiap 3 atau 4 hari sekali dan juga mencampurkan beberapa jenis pestisida dalam satu aplikasi (Joko et al 2017).…”
unclassified